PENDAMPINGAN PENULISAN PROPOSAL PENELITIAN TINDAKAN KELAS DAN ARTIKEL ILMIAH BAGI GURU DI SMAN 3 PALEMBANG - Dewi Koryati; Dewi Pratita; Siti Fatimah; Ikbal Barlian; Edutivia Mardetini (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2019)
Classroom Action Research (CAR) is a study of teacher activities related to professional development in the class. The aims to improve the real and practical problems in improving the quality of classroom learning. Scientific articles are reports of research results presented and published in a recognized (accredited) scientific magazine (journal). The mentoring was conducted for four months at SMAN 3 Palembang. Beginning with a discussion of the learning issues facing the economics teacher then devising a plan to implement the CAR into the learning plan and practice it. During the implementation of the CAR, teachers practise observing, analyzing and evaluating the outcome of actions and then re-planning the second phase of action. In the second cycle the target of learning outcomes is achieved. The next practicing economy teachers compose the report in the form of scientific articles. Lastly, theresults of the mentoring activity of the economics of X-grade social sciences 4 at SMAN 3 Palembang was socialized to the management group of MGMP Economics in Palembang. The conclusion of this mentoring program demonstrates an increase in the understanding of economic teachers; 1) Implement a discovery learning model for economic learning, 2) Write a CAR proposal and apply it in class, 3) Write scientific articles sourced from the results of the CAR.